071 Actigraphy-Derived Sleep Metrics are Not Related to Central Hemodynamics or Arterial Stiffness in Healthy Adults. (3rd May 2021) - Culver, Meral; Montoye, Alexander; McMillan, Nathan; Cross, Brett; Riemann, Bryan; Flatt, Andrew; Grosicki, Gregory
Abstract: Introduction: Insufficient sleep is an emerging risk factor for cardiovascular disease. To evaluate the hypothesis that decrements in vascular function, due to poor sleep, may serve as a mechanistic link between sleep and cardiovascular disease, we explored relationships of actigraphy-derived sleep metrics with central hemodynamics and arterial stiffness in healthy young adults. Methods: A total of 23 women and 27 men (23±5 yrs), free of known cardiovascular, metabolic, and renal disease, and not using sleep medication, participated in this study. ActiGraph GT9X wrist-worn accelerometers were used to measure sleep efficiency, total sleep time, wake after sleep onset, and number of awakenings over a seven-day period. Vascular health measures including central pressures and augmentation index at a heart rate of 75 beats per minute (AIx@75) were quantified via pulse wave analysis, and carotid femoral pulse wave velocity (cf-PWV) was assessed using applanation tonometry. Gender-specific z-scores for each of the sleep metrics were summed to assign each participant a "sleep score" (higher score = better sleep), and relationships between sleep scores and vascular health measures were explored using Pearson correlation coefficients. Results: In men, sleep score (range: -4.92 to 9.10) was not related (P>0.05) to central systolic (114±15 mmHg, r=-0.26) or diastolic (72±7 mmHg, r=-0.21) pressures. Similarly, in women, sleep score (range: -5.02 to 5.34) was not related (P>0.05) to central systolic (103±11 mmHg, r=-0.09) or diastolic (72±10 mmHg, r=-0.21) pressures. Sleep score also failed to predict (P>0.05) indices of arterial stiffness, AIx@75 (men = 3.1±12.3, r=0.04; women = 5.2±9.5, r=-0.25) and cf-PWV (men = 6.2±0.8 m/s, r=-0.12; women = 5.7±0.5 m/s, r=-0.10). Conclusion: In young healthy individuals, actigraphy-derived sleep characteristics were not related to central hemodynamics or non-invasive indices of arterial stiffness. Previously documented relationships between sleep and vascular function may be limited to less healthy populations, poorer sleepers, or only for certain sleep metrics. Support (if any):